"Hiropumi Ito and his role in the Japanese reform movement (Meiji era 1841-1909) "Historical Study - Al-Rawi, Khansaa Zaki Shams Al-Din; Tamimi, Wassam Hadi Akkar (Journal of Humanities & Social Sciences, 2019)
It provoked the reform movement that took place in Japan era (Meiji Meiji- enlightened judgment), in the nineteenth century, the great admiration and great interest from the presence of some researchers, trying to decipher the secrets of the success of the Japanese experience and superiority dazzling and fast on the rest of the world. Some might gather that the success of that experience is the result of a vehicle and a complex of social, economic, political, intellectual and cultural developments experienced by Japan since the seventeenth century, invested by reform leaders and became the starting point of the Renaissance and modern Japanese point of strength. The highlight of the reform leaders in the Meiji era is (Hirobumi Ito), who make unremitting efforts to promote Japan all the magazines for their arrival into the ranks of major powers at the time. Accordingly, the search section on three axes, first touched on the upbringing, education and positions Tolha Hirobumi Ito even in 1881, and the second dealt with his contribution to the age of the Japanese Constitution in 1889, while said third axis his role as prime minister and end his political career in 1909.
Keywords: Hirobumi Ito; reform; Meiji